Peter the Great's Venetian Policy and the Prut Campaign - A. O. Yastrebov (Vestnik MGIMO-Universiteta)
Russia's regular contacts with the Republic of Venice on the eve of the RussianTurkish war 1710-1713 resumed after almost a ten-year break. Before Sultan Ahmed III declared war, the Tsar sent two letters to the doge. They can be interpreted as a call to Venice to recognize the intermediate results of the Northern War and as an appeal to the republic's orthodox subjects to join Russia in the impending conflict. This episode is scarcely covered in Russian and international historiography. The connection of the envoys with the Prut campaign is also not covered in the literature. Therefore, it seems necessary to establish a connection between the two events, especially in changes in Russian foreign policy towards Venice.In March 1711, a Russian consul was sent to Venice to build support and attract volunteers for the opening theater of military operations in the Balkans. It is no coincidence that Dmitry Bozis became the first Russian consul in Italy. Being a prominent representative of the Greek community of the capital, he successfully extended his influence not only to the local Greeks but also to the Slavs of Dalmatia, who wanted to serve the Russian Tsar and fight the Turks. The outcome of the Prut campaign did not affect the consulate's work and the trade mission. Agents of the Russian government, who had commercial orders, were sent to Venice, and successfully fulfilled their mission. One of them was Count Savva Raguzinsky, an outstanding diplomat and successful commercial agent. His activities were relatively peaceful, although they still included political monitoring and legal intelligence.The resumption of bilateral relations caused by the Prut operation positively affected Russian-Venetian relations. Since the departure of the consul Bozis and the diplomatic agent Caretta, who had the authority to create a second Balkan "front" in the rear of the Sultan, after July 12, 1711, the Russian mission transformed into a commercial agency with broad diplomatic powers. These changes open a new, fruitful period in the history of bilateral relations between Russia and Venice.